Bronchial Stenosis Distal To The Anastomosis In A Patient With Bilateral Lung Transplantation: A Case Report (2016)
The airway complications after Lung Transplatation (LT) usually occur in the anastomosis. The bronchial stenosis distal to the anastomosis (BEDA) or evanescent bronchus syndrome is the symptomatic stenosis or complete atresia of the intermediate bronchus, which presents during the first six months post transplantation associated with high morbidity and mortality with a mean survival of 25 months after the diagnosis, it is associated to acute rejection, infection and ischemic damage, treatment involves repeated dilations and stent. Ojectives: To describe a BEDA in the right lung in bilateral LT, with post transplant follow-up in Fundación Valle del Lili.